Pendampingan bagi Balita Stunting dalam Pemberian Makanan Tambahan di Kecamatan Cempaka Putih - Chindy Amir; Maharani Kusuma Dewi (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
Stunting, as a chronic nutritional problem, remains a significant public health challenge in Indonesia, particularly among toddlers. This condition is characterized by impaired linear growth caused by prolonged malnutrition. In Cempaka Putih Subdistrict, based on field observations, toddlers with undernutrition and stunting are still found. Additionally, mothers’ limited understanding of providing nutritious complementary foods (PMT) is a major concern. Therefore, this community service activity aims to improve mothers’ knowledge regarding balanced nutrition and stunting prevention through guidance on providing complementary foods. The methods used included interactive education sessions, guidance on the provision of supplementary feeding, and anthropometric examinations. The results of the activity showed a 45% increase in mothers’ knowledge, improvements in growth among some toddlers, and the conclusion that community-based guidance is effective in supporting stunting prevention